23. STRESS AND STRESS-RELATED FACTORS TO STUDENTS AT YEN LANG HIGH SCHOOL, ME LINH DISTRICT, HANOI, IN 2022 (Vietnam Journal of Community Medicine, 2024)
Purpose: This study aimed to (i) assess the genre of students’ stress and (ii) analyze stress-related factors at Yen Lang High School, Me Linh – Hanoi, in 2022.Method: The research method of epidemiology with a descriptive cross-sectional study design was selected. Three hundred ninety-six students of the High School were sent a survey to complete. DASS-21 toolkit was used to evaluate and extract the final result of the research.Results: 10,4% of students showed signs of stress at the low, moderate, and high levels as of 5.6%, 4.0%, and 0.8%, respectively. There was no performance of extremely high-stress levels in the research result. Some stress-related factors were indicated as follows: Regular exercise; internet addiction; relationship with friends; insomnia after being infected with covid -19; emotional disturbances after being infected with covid -19; memory loss after being infected with covid -19; study pressure; pressure from examination and final test; general academic pressure.Conclusion:- The proportion of depression-related students accounts for 10.4% at three levels, including mild, moderate and severe which were 5.6%, 4.0% and 0.8% respectively.- Some stress-related factors to students: Regularly exercising (OR= 2.3, p < 0.05); Internet addiction (OR= 4.68, p < 0.05); Relationships with friends (OR = 6.29, p < 0.05); Post-covid19 insomnia (OR = 2.52, p < 0.05); Symptoms of post-covid19 emotional disorders (OR = 3.95, p < 0.05); Symptoms of post-covid19 memory decline (OR = 3.6, p < 0.05); Experiencing academic pressure (OR= 3.69, p < 0.05); Academic Performance Pressure (OR= 5.2, p < 0.05).
Keywords: Depresion; Stress.